O moralnych obowiązkach ludzi wobec zwierząt. Etyka Gary’ego Francione - Dorota Probucka (Studia Ecologiae et Bioethicae, 2015)
The purpose of my article is to present and analyze the ethical views of Gary Francione – the leading, contemporary representative of the Animal Rights Movement. He built his theory by criticizing the views of two other supporters of the idea of animal liberation: Peter Singer and Tom Regan. In his opinion, neither of these philosophers did not escape from the anthropocentric paradigm binding the moral obligations to animals with the primacy of human interest. Singer believed that only humans have the ability to plan their own future, and only they want to live and extend their own existence. While according to Regan, in conflict situations, respect for human interest should be dominant. Francione agrees that only people understand a deeper meaning of their own existence, but it does not follow that only they want to live and do not want to die. The need to preserve and continue life is not the result of mental states, but it is a consequence of sensitivity – the biological trait which aims to safeguard and continuation of life. According to Francione, if every sensitive creature has an interest in preserving his own life and avoiding suffering it they also have a moral right to life and not being treated in a cruel manner.